2007
DOI: 10.1111/j.1539-6924.2007.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

What Risks Do People Perceive in Everyday Life? A Perspective Gained from the Experience Sampling Method (ESM)

Abstract: The experience sampling method (ESM) was used to collect data from 74 part‐time students who described and assessed the risks involved in their current activities when interrupted at random moments by text messages. The major categories of perceived risk were short term in nature and involved “loss of time or materials” related to work and “physical damage” (e.g., from transportation). Using techniques of multilevel analysis, we demonstrate effects of gender, emotional state, and types of risk on assessments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
3
19
2
Order By: Relevance
“…On average, participants responded between zero and ten minutes after reception (overall mean of one minute). The distribution of types of activities and risks was similar to a previous study (Hogarth, Portell, & Cuxart, 2007) and is not presented here. Table 1 reports HLM results of regressing perceived risk on mood and emotional reactions as well as gender.…”
Section: Resultssupporting
confidence: 66%
“…On average, participants responded between zero and ten minutes after reception (overall mean of one minute). The distribution of types of activities and risks was similar to a previous study (Hogarth, Portell, & Cuxart, 2007) and is not presented here. Table 1 reports HLM results of regressing perceived risk on mood and emotional reactions as well as gender.…”
Section: Resultssupporting
confidence: 66%
“…Other research topics studied in college settings through daily experience data methods have included motivators of alcohol use (Hussong, 2003), and events evoking social anxiety (M. R. Lee, Okazaki, & Yoo, 2006). In their study of risk perceptions among college students, Hogarth, Portell, and Cuxart (2007) used an event-based ESM design, but utilized students' own mobile phones rather than providing pagers. In that study, participants were supplied with questionnaires that they were asked to complete whenever they received a text message from the researcher.…”
Section: The Experience Sampling Methodsmentioning
confidence: 99%
“…As we saw in the examples of Shephard et al (2006) and Hogarth et al (2007), they allow testing to be done "in the field," where it would be harder to test using a traditional computer-based setup. Shephard et al used the extreme example of testing in space, but also suggested that there may be down-to-earth scenarios that could be explored using mobile devices.…”
Section: Advantages and Disadvantages Of Mobile Phones In Psychologicmentioning
confidence: 99%
“…It would therefore be possible to do as Hogarth et al (2007) did and contact people, or ask them to respond at a specific time. Thus, the effect of circadian rhythms could easily be investigated.…”
mentioning
confidence: 99%